The Management of Depression in Post-Stroke Patients - Azahra, Devitania; Aini, Syarifah; Sinulingga, Sadakata (Faculty of Medicine, Universitas Airlangga, 2026)
Introduction: Among stroke survivors, psychiatric complications such as post-stroke depression (PSD) are common, affecting about a third of stroke survivors. Antidepressant therapy is regarded as the preferred approach for treating depression. However, it is important to study other treatments that can also be effective besides antidepressants. Further research is needed to review available studies regarding the management and treatment of post-stroke depression to reduce depression rates in post-stroke patients. Therefore, a systematic review was carried out on the treatment of depression in post-stroke patients. This study aims to identify the different types of post-stroke depression management. Methods: This systematic review was analyzed using the PRISMA-P 2015 method. A literature search was conducted from March 17 to 24, 2023, in electronic-based national and international databases, PubMed and ScienceDirect, with the keywords “Therapy” AND “Post-Stroke Depression” and “Management” AND “Post-Stroke Depression,” as well as additional journals from Google Scholar based on predefined inclusion and exclusion criteria. Results: Based on the search results, 20 relevant articles met the criteria for analysis in this study. The analysis results show various effective interventions that can reduce depression rates in post-stroke patients, such as medical ministry logotherapy psychotherapy, transmagnetic stimulation therapy, exercise therapy, Slow Stroke Back Massage (SSBM), various types of acupuncture and electroacupuncture, light exposure sunlight therapy, cognitive and psychosocial behavioral therapy, music therapy, moxibustion therapy, repetitive transcranial magnetic stimulation, and virtual-reality-based interventions, as well as herbal medicines and antidepressants. Conclusion: Treatment for patients with post-stroke depression varies, pharmacologically and non-pharmacologically.